Moral (and Ethical) Realism - Richards, H (Taylor and Francis Ltd., 2019)
This article advocates a naturalist and realist ethics of solidarity. Specifically, it argues that human needs should be met; and that they should be met in harmony with the environment. Realism should include respect for existing cultures and the morals presently being practiced–with reasonable exceptions. Dignity must come in a form understood and appreciated by the person whose dignity is being respected. It is also argued that naturalist ethics are needed to combat liberal ethics, not least because the latter supports today’s inflexible and dysfunctional institutions. In arguing for these positions, reference is made to the naturalist realist ethics of Georges Canguilhem, C.H. Waddington, John Dewey and David Sloan Wilson, all of whom embed the social order in the natural order. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.